A Cryptic Invader of the Genus Persicaria (Polygonaceae) in La Palma and Gran Canaria (Spain, Canary Islands) - Filip Verloove; Rainer Otto; Steven Janssens; Sang-Tae Kim (Diversity, 2021)
A cryptic invader of the genus Persicaria has recently increased in the damper, northern parts of La Palma and Gran Canaria in the Canary Islands (Spain) and locally behaves as an invasive species. Examination of historical herbarium specimens showed this species to be present in Gran Canaria since the 1960s and the same probably applies to La Palma. Up to now, this species had been assigned to the Old World weed P. maculosa. However, morphologically, these plants clearly correspond with P. hydropiperoides, a common and widespread weed native to the New World, and indeed morphologically similar to P. maculosa. Diagnostic features for these two species, as well as for another similar species (P. decipiens, originally described from the Canary Islands), are compared, thoroughly discussed, and copiously illustrated. The current distribution, ecology, and naturalization status of P. hydropiperoides in the Canary Islands are also assessed. The variability of P. hydropiperoides is discussed, more precisely the taxonomic position of a southern ‘race’ of it that is sometimes referred to as a distinct species, P. persicarioides, and to which the Canarian plants belong. The taxonomic value of the latter appears to be clear, although at a lower level. A new combination, at varietal rank, is proposed and validated. In addition to our morphology-based study, a molecular phylogenetic analysis has been conducted on the nuclear ITS region and the plastid DNA region trnL-F.